Optimal design of Electric Power Assisted Steering system (EPAS) using GA-PID method - Hassan, Mohd Khair; Mohd Azubir, Nor Aziah; H. M. I., Nizam; Toha, Siti Fauziah; Ksm Kader Ibrahim, Babul Salam (Elsevier, 2012)
The introduction of Electric Power Assisted Steering (EPAS) system is gradually replacing the conventional steering system in modern cars. The main advantage of EPAS system is the ability to minimise energy consumption. This paper discusses the implementation of GA-PID algorithm to realise the potential of energy reduction as compared to conventional PID method. A brushes DC motor is mounted on the steering column to provide an assist torque to the driver. This configuration is known as C-type EPAS system. The results have shown GA-PID controller is bale to minimize energy consumption as compared to PID controller.